Analisis Framing Model Robert Entman tentang Pemberitaan Kasus Korupsi Bansos Juliari Batubara di Kompas.com dan BBCIndonesia.com - Intan Leliana; Herry herry; Panji Suratriadi; Edward Enrieco (Cakrawala - Jurnal Humaniora, 2021)
Corruption is a pervasive global problem with detrimental effects on economic performance, political stability and community integration. Corruption has provided its own moment for the mass media which includes electronic mass media and printed mass media today to be used as the latest news which is called the Headline (headline). One of the news that discusses the new corruption case is the case of Social Assistance Funds (Bansos) at the Ministry of Social Affairs. The Corruption Eradication Commission (KPK) which has appointed the Minister of Social Affairs (Mensos) Juliari Batubara as a suspect in the corruption of social assistance (Bansos) for residents affected by the Covid 19 pandemic. The method in this study uses a qualitative description which aims to describe systematically, factually, and accurately about news on the corruption case of Social Affairs Minister for Social Affairs Juliari Batubara in Kompas.Com and BBCIndonesia.com with framing Robert Entman analysis. The results of this study are based on the results of the framing analysis in this study, it is very clear that the role of the media is not limited to conveying information, the times demand the media to play the role of 'watch dog' or guard dog and control for the government and related institutions in formulating every policy. for the benefit of society. The results of the study show that the media Kompas.com and BBCIndonesia.com provide space for information and clarification for the government and the KPK to make all efforts to curb and overcome the problem of corruption in covid 19 social assistance funds. Keywords: Corruption, Framing, Bansos